Dry-process high-load composite positive electrode sheet with gradient distribution and preparation method thereof
By adopting a high-load composite positive electrode sheet preparation method with gradient distribution in the dry electrode process, the problems of uneven dispersion of conductive agents and binders and long transmission paths of thick electrodes are solved, and the high load and high electrodes of electrode materials are achieved The capacity is exerted, which improves the energy density and cycle stability of the battery.
Patent Information
- Application Number
- CN202411279189.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-12
AI Technical Summary
The existing dry electrode process is difficult to achieve uniform dispersion of conductive agents and binders during processing, resulting in insufficient strength of the electrode diaphragm, poor film formation, uneven distribution of conductive agents, and affecting electrical performance. At the same time, the electron and ions transport paths in the thick electrode are long and the conduction is slow, resulting in too large polarization of the electrode sheet and the electrochemical properties of the electrode material cannot be fully utilized.
The preparation method of dry high-load composite positive electrode sheet with gradient distribution is adopted, and the gradient preparation of the electrode diaphragm set is realized through step-by-step mixing, prefibrosis process and efficient shear mixing technology. The specific steps include premixing, stirring, Insulation, supersonic air flow treatment and multi-stage heat roller treatment are formed to form the first and second electrode diaphragms, and heat roller treatment is carried out with the array through-hole coating aluminum foil current collector.
Through the gradient-distributed electrode material structure, the diffusion rate of lithium ions in the electrode is improved, and a more uniform electric field distribution is formed, which solves the problem of poor rate performance of the electrode sheet, enhances the adhesion between the electrode diaphragm and the current collector, and prevents the electrode sheet from falling off. , improve the energy density and cycle stability of the battery.
Smart Images

Figure CN118841522B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular, relates to a dry-process high-load composite positive electrode sheet with gradient distribution and a preparation method thereof. Background Art
[0002] Improving the energy density of liquid lithium-ion batteries is a key demand and important driving force for battery development. Batteries with higher energy density can store more energy in a smaller volume and weight, which not only reduces the overall weight of electric vehicles and improves their performance and handling, but also makes portable electronic devices lighter and enhances the user experience. In addition, improving energy density also helps to reduce the cost of batteries, because the cost per unit of energy decreases with the increase of energy density. Therefore, battery manufacturers and researchers are committed to continuously improving the energy density of liquid lithium-ion batteries by developing new battery materials and corresponding battery systems with higher specific capacity or voltage platforms, developing more advanced battery structure designs, and optimizing battery manufacturing processes.
[0003] In recent years, solvent-free dry processes have been widely studied for the preparation of thick electrodes, which usually involve mixing the positive electrode active material, conductive agent and solid binder, fiberizing them, and then hot rolling them into a self-supporting film and then compounding them with the current collector. The dry positive electrode process can effectively control the electrode thickness and uniformity of thick electrodes. It has unique advantages in the preparation of thick electrodes and is suitable for the preparation of ultra-high loading electrodes. The dry positive electrode process is considered to be an important development direction in the field of lithium-ion battery manufacturing due to its advantages in improving battery performance, reducing costs and environmental friendliness. However, there are still some problems that need to be solved in the dry positive electrode process:
[0004] 1. In the existing dry electrode process, no solvent is used during the processing, and it is difficult to achieve uniform dispersion of the conductive agent and the binder in the positive electrode powder. Under this condition, the binder is further fibrillated, which will cause excessive or insufficient local fibrillation of the binder in the powder, resulting in insufficient binder fibrillation, insufficient electrode membrane strength, poor film-forming properties, and uneven distribution of the conductive agent, resulting in increased surface resistance and weak strength of the electrode membrane, which in turn affects the electrical properties of the electrode membrane. It is necessary to use higher-performance fibrillation equipment and mixing equipment.
[0005] 2. The fibrillation process of PTFE is very sensitive to temperature and shear force, and it is difficult to accurately control the formation of a uniform self-supporting film.
[0006] 3. Although the existing dry process can effectively control the thickness and uniformity of the electrode, it cannot simultaneously solve the difficult problems of long electron and ion transmission paths and slow conduction in thick electrodes, resulting in excessive polarization of the electrode piece and inability to fully exert the electrochemical properties of the electrode material.
[0007] 4. The existing dry process prepares the electrode membrane by hot rolling treatment of the mixed powder, and then composites it with carbon-coated aluminum foil by hot rolling. However, due to the poor adhesion between the electrode membrane and the current collector, it leads to a large interface impedance and even film peeling. Summary of the invention
[0008] In view of the above problems, the present invention provides a dry-process high-load composite positive electrode plate with a gradient distribution and a preparation method thereof. The positive electrode plate prepared by the preparation method includes an outer first electrode membrane, an inner second electrode membrane and an array-type through-hole carbon-coated aluminum foil current collector close to the inner layer. From the first electrode membrane to the second electrode membrane, the mass proportion of the solid electrolyte gradually decreases, while the mass proportion of the conductive agent and the binder gradually increases, thereby realizing the gradient preparation of the electrode membrane group, improving the diffusion rate of lithium ions in the electrode, and forming a more uniform electric field distribution inside the positive electrode, solving the problem of poor rate performance of the plate caused by thick electrodes, effectively improving the adhesion between the electrode membrane and the current collector, and preventing the plate from falling off.
[0009] In one aspect, the present invention provides a method for preparing a dry high-load composite positive electrode sheet with a gradient distribution, the preparation method comprising the following steps:
[0010] Step 1: premixing the conductive carbon material, oxide solid electrolyte particles of various particle sizes, and the positive electrode active material in a certain proportion, and dispersing them at a stirring speed of 5000-10000 r / min to obtain a first powder;
[0011] Step 2: adding a certain amount of binder to the first powder, dispersing the mixture under the conditions of a stirring speed of 200-800 r / min and a stirring temperature of 0-10° C. to obtain a second powder;
[0012] Step 3: heat-treating the second powder at a temperature of 90-200° C. to obtain a pre-fiberized second powder;
[0013] Step 4: using a supersonic airflow with a speed greater than 300 m / s to treat the second powder after heat preservation, fiberizing the binder material, and uniformly dispersing and coating the conductive carbon material and multi-size oxide solid electrolyte particles on the surface of the positive electrode active material particles to form a third powder coated with a fiberized binder;
[0014] Step 5: performing a multi-stage hot roller pressing process on the third powder to obtain a first electrode membrane;
[0015] Step 6: Repeat the method of steps 1-5, gradually adjust the ratio of different components in the first electrode membrane, and prepare a second electrode membrane;
[0016] Step 7: stacking the carbon-coated aluminum foil current collector, the first electrode membrane, and the second electrode membrane in sequence, and performing hot roller pressing treatment to obtain a high-load composite positive electrode sheet with a gradient distribution;
[0017] In step 1, the particle sizes of the plurality of oxide solid electrolytes include at least two types: micron particles and nanoparticles;
[0018] In step 6, the mass proportion of the binder and the conductive carbon material of the second electrode membrane is greater than the mass proportion of the binder and the conductive agent of the first electrode membrane, and the mass proportion of the oxide solid electrolyte particles of the second electrode membrane is less than the mass proportion of the oxide solid electrolyte particles of the first electrode membrane;
[0019] In step 7, an array-type through-hole structure is provided on the carbon-coated aluminum foil current collector.
[0020] Furthermore, the amount of conductive carbon material added is 1-6wt% of the mass of the high-loaded composite positive electrode sheet, the amount of the mixture of oxide solid electrolyte particles of various particle sizes added is 1-10wt% of the mass of the high-loaded composite positive electrode sheet, the amount of positive electrode active material added is 77-96wt% of the mass of the high-loaded composite positive electrode sheet, and the amount of binder added is 2-7wt% of the mass of the high-loaded composite positive electrode sheet.
[0021] Furthermore, the particle size range of the micron particles is 1-5 μm, the particle size range of the nanoparticles is 100-600 nm, and the mixing ratio of the nanoparticles to the microparticles is in the range of 5:1-1:1.
[0022] Furthermore, the conductive carbon material in step 1 adopts a carbon material with a high aspect ratio and high conductivity.
[0023] Furthermore, in step 1, the stirring time is 30-300 min, and the stirring temperature is room temperature; in step 2, the stirring time is 10-60 min.
[0024] Furthermore, the holding time in step 3 is 2-10 h; and the working temperature of the heating roller in step 5 is 150-250°C.
[0025] On the other hand, the present invention provides a dry-process high-load composite positive electrode plate with a gradient distribution, which is prepared by any of the preparation methods described above; it includes an electrode membrane group and an array-type through-hole carbon-coated aluminum foil current collector close to the inner layer of the electrode membrane group; the electrode membrane group includes a first electrode membrane arranged on the outer layer and a second electrode membrane located on the inner layer.
[0026] Furthermore, the gradient distribution of the dry-process high-load composite positive electrode sheet is that the mass proportion of the oxide solid electrolyte particles gradually decreases from the first electrode membrane to the second electrode membrane, and the mass proportion of the conductive carbon material and the binder gradually increases from the first electrode membrane to the second electrode membrane; the thickness of the dry-process high-load composite positive electrode sheet is 30-500μm.
[0027] The beneficial effects of the present invention are:
[0028] First, in order to solve the problem of difficult diffusion of ions and electrons in thick electrodes and electrode membrane peeling, the present invention sets a multi-gradient electrode sheet structure, constructs a gradient distribution of conductive agent, solid electrolyte and binder inside the positive electrode sheet, realizes high loading and high capacity of active materials, and helps to improve the energy density of the battery; the sheet is divided into an outer first electrode sheet and an inner second electrolyte sheet, wherein from the diaphragm to the current collector, the mass proportion of the solid electrolyte gradually decreases, and the mass proportion of the conductive agent and the binder gradually increases, and the high content of solid electrolyte in the first electrode sheet can construct a continuous ion transmission channel inside the sheet, thereby improving the diffusion rate of lithium ions in the electrode; the high conductive agent content of the second electrode sheet The content can improve the conductivity of the inner film, help the electrons at the current collector to quickly enter and exit the electrode film, and help to form a more uniform electric field distribution inside the positive electrode, solving the problem of poor rate performance of the electrode caused by thick electrodes; the gradient distribution of the binder in the positive electrode can enhance the adhesion between the electrode film and the current collector, improve the structural stability of the electrode, and at the same time adjust the pore structure of the electrode and optimize the infiltration of the electrolyte of the outer electrode film. In addition, the gradient distribution of the solid electrolyte powder inside the electrode can create a continuous ion transmission channel, thereby increasing the diffusion rate of lithium ions in the electrode, while enhancing the structural stability of the electrode and improving the low temperature performance and cycle performance;
[0029] Second, the present invention adds micron- and nano-sized oxide solid electrolyte particles to the positive electrode membrane. By matching large and small particles, small particles can be tightly wrapped on the surface of the positive electrode active material, and large particles can shorten the ion transmission path, reduce the number of particle interfaces, improve the interface contact between the solid electrolyte and the electrode material, and help to form a uniform lithium ion channel at the electrolyte and electrode interface, reduce the interface resistance, and shorten the ion transmission path, build an efficient ion transmission network, so that the composite high-load positive electrode sheet has excellent rate charging and discharging performance, low temperature performance and long cycle life; high aspect ratio, high conductivity carbon nanomaterials can be evenly wrapped on the surface of the active material, and a continuous and efficient superconducting network can be built inside the thick electrode sheet to achieve rapid transmission of electrons, which can reduce polarization and structural changes of the positive electrode material during the charging and discharging process, improve the cycle stability and safety of the battery, and accelerate the charging and discharging process of the battery, so that the electrode can withstand a larger current;
[0030] Third, the present invention solves the problem of poor adhesion between the dry electrode membrane and the current collector interface and easy membrane peeling. The present invention is different from the existing technical solutions. The carbon-coated aluminum foil current collector used is processed with regularly arranged tiny through holes on the carbon-coated aluminum foil current collector by physical or chemical methods to form an array structure, which increases the contact area between the current collector and the electrode material and the roughness of the current collector surface, improves the adhesion and stability between the electrode membrane and the current collector, avoids the problem of falling off during charging and discharging, reduces the interface resistance, reduces the internal resistance of the battery, and reduces the polarization problem of the pole piece, thereby improving the battery's rate charging and discharging performance and cycle stability. The through-hole structure helps the electrolyte to quickly infiltrate and penetrate deeper into the thick electrode, improves the contact between the electrolyte and the electrode, and is beneficial to improving the battery's charging and discharging performance. In addition, after the through-hole carbon-coated aluminum foil is treated with pores, the weight of the current collector is greatly reduced, which can effectively improve the battery's energy density;
[0031] Fourth, the present invention uses step-by-step mixing, pre-fiberization process and efficient shear mixing technology to make the binder evenly distributed and fully fiberized in the positive electrode sheet to form a three-dimensional network structure, which is conducive to the uniform distribution and adhesion of the remaining components, and the particles are tightly wrapped in the three-dimensional network to form a uniform electrode structure, which can reduce polarization during charging and discharging, while improving the mechanical strength and structural stability of the electrode, and help improve the cycle stability of the electrode. At the same time, the efficient shear mixing technology, through the high shear force of the supersonic airflow pulverizer, opens the agglomerates of carbon nanomaterials and oxide solid electrolytes, so that they are evenly coated on the surface of the positive electrode material, constructs a full range of ion and electron transmission channels, reduces the internal resistance of the electrode, and improves the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a flow chart of the method for preparing the dry high-load composite positive electrode sheet with gradient distribution of the present invention;
[0033] Figure 2 is a cross-sectional SEM image of a dry high-load composite positive electrode sheet according to an embodiment of the present invention;
[0034] Figure 3 This is a cycle performance diagram of the dry high-load composite positive electrode sheet of Example 1 of the present invention;
[0035] Figure 4 Specific capacity-voltage curves of dry-process high-load composite positive electrode sheets of Example 1 and Comparative Example 1 of the present invention;
[0036] Figure 5 1 is a cycle performance curve and a capacity retention curve of the dry-process high-load composite positive electrode sheet of Example 1 and Comparative Example 1 of the present invention;
[0037] Figure 6It is a comparison chart of the rate performance of the dry-process high-load composite positive electrode sheets of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0038] In order to enable those skilled in the art to better understand the technical solution of the present application, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0039] The terms such as up, down, left, right, front and back in this application document are based on the positional relationships shown in the drawings. If the drawings are different, the corresponding positional relationships may also change accordingly, so they cannot be understood as limiting the scope of protection.
[0040] In this application, the terms "install", "connected", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, an integral connection, a mechanical connection, an electrical connection, or mutual communication, a direct connection, or an indirect connection through an intermediate medium, the internal connection of two components, or the interaction relationship between two components. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0041] Refer to the instruction manual Figure 1 The present invention describes a dry high-load composite positive electrode sheet with gradient distribution and a preparation method thereof. The specific steps of the preparation method are as follows:
[0042] Step 1: premix the conductive carbon material, oxide solid electrolyte particles of various particle sizes, and the positive electrode active material in a certain proportion to obtain a mixed material, and use high-speed dispersion to process the mixed material to obtain a uniformly mixed first powder.
[0043] Specifically, step 1 uses a powerful mixer, such as a high-speed dispersing device, to add the conductive carbon material, oxide solid electrolyte particles of various particle sizes, and positive electrode active materials to the high-speed dispersing device in a certain proportion, and utilizes the strong shear force of the high-speed dispersing device to break up and disperse the agglomerates of the conductive carbon material and the various oxide solid electrolyte particles, so that the conductive carbon material, oxide solid electrolyte particles of various particle sizes, and the positive electrode active materials are evenly mixed.
[0044] In step 1, the amount of conductive carbon material added is 1-6wt% of the mass of the electrode membrane, the amount of the mixture of oxide solid electrolyte particles of various particle sizes added is 1-10wt% of the mass of the electrode membrane, and the amount of positive electrode active material added is 77-96wt% of the mass of the electrode membrane.
[0045] The rotation speed of the high-speed dispersion in step 1 is 5000-10000 r / min, the stirring time of the mixed material is 30-300 min, and the mixing temperature is room temperature.
[0046] The conductive carbon material is a carbon material with a high aspect ratio and high conductivity. Preferably, the conductive carbon material is one or more of graphene, carbon nanotubes, and carbon nanofibers, but is not limited thereto.
[0047] The oxide solid electrolyte includes one or more of a perovskite oxide solid electrolyte, a garnet oxide solid electrolyte, and a NASICON ((Na+Site-Isolated CONductor)) oxide solid electrolyte, but is not limited thereto. Preferably, the perovskite oxide solid electrolyte is selected from lithium lanthanum titanium oxide; the garnet oxide solid electrolyte is selected from one or more of lithium lanthanum zirconium oxide, niobium-doped lithium lanthanum zirconium oxide, tantalum-doped lithium lanthanum zirconium oxide, and niobium-tantalum dual-doped lithium lanthanum zirconium oxide; the NASICON oxide solid electrolyte is selected from one or more of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, and lithium yttrium titanium phosphate.
[0048] The particle sizes of the various oxide solid electrolytes include at least micron particles and nanoparticles. Preferably, the particle size of the micron particles is in the range of 1-5 μm, the particle size of the nanoparticles is in the range of 100-600 nm, and the mixing ratio of the nanoparticles to the micron particles is in the range of 5:1-1:1.
[0049] It should be noted that the present invention does not limit the type of positive electrode active material. All commonly used positive electrode active materials in the art are suitable for the present invention, which may be doped positive electrode active materials, undoped positive electrode active materials, or coated modified positive electrode active materials.
[0050] The positive electrode active material is the main material of the first powder. Preferably, the positive electrode active material includes: lithium nickel cobalt manganese oxide (LiNi x Co y Mn 1-x-y O2), lithium nickel cobalt aluminum oxide (LiNi x Co y Al 1-x-y O2), lithium iron phosphate (LiFePO4), lithium iron manganese phosphate (LiMn x Fe 1-x PO4), lithium manganese oxide (LiMnO2) and lithium cobalt oxide (LiCoO2), but not limited thereto.
[0051] Step 2: Add a certain amount of binder to the first powder, and use low temperature and low speed conditions to disperse and evenly mix the binder and the first powder to obtain a second powder.
[0052] Specifically, step 2 uses a powerful mixer, such as a high-speed dispersing device. On the basis of step 1, a certain amount of binder is added to the first powder of the high-speed dispersing device, the rotation speed of the high-speed dispersing device is reduced, and a smaller shear force is used to achieve uniform dispersion of the binder in the first powder. At the same time, the temperature of the stirring tank of the high-speed dispersing device is reduced, and stirring is performed within a certain stirring time to obtain the second powder. Since the binder is highly sensitive to temperature and shear force, the binder can be prevented from being prematurely fiberized in this process by low temperature and low speed. If the binder is fiberized prematurely, it is difficult for the binder to be uniformly dispersed in the first powder, resulting in excessive or insufficient local binder, which affects the strength of the electrode membrane.
[0053] The binder includes one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), poly(vinylidene fluoride-hexafluoropropylene) (PVDF-HFP), polyacrylic acid (PAA), polyvinyl alcohol (PVA) and polyacrylonitrile (PAN), but is not limited thereto. Preferably, the binder is PTFE.
[0054] The amount of binder added in step 2 is 2-7wt% of the mass of the electrode membrane.
[0055] In step 2, the rotation speed of the high-speed dispersing device is 200-800 r / min, the mixing time of the binder and the first powder is 10-60 min, and the temperature of the mixing tank of the high-speed dispersing device is controlled at 0-10°C.
[0056] Step 3: The second powder is subjected to a heat preservation treatment at a certain temperature to obtain a pre-fiberized second powder.
[0057] Since the surface temperature of the second powder mixed at low temperature in step 2 is reduced, it cannot maintain sufficient fluffiness, which will lead to insufficient fiberization of the subsequent second powder. There is a risk of breakage and powder loss during subsequent rolling. Therefore, before the second powder is subjected to the fiberization process, the powder needs to be pre-fiberized to transform the binder crystals in the powder into a soft and fluffy state.
[0058] Specifically, step 3 uses a high-temperature oven, places the second powder in the high-temperature oven, and uses the high sensitivity of the binder to temperature to keep the second powder warm at a temperature of 90-200° C. for 2-10 h.
[0059] Step 4: Use supersonic airflow to treat the second powder after heat preservation, fiberize the binder in the second powder, and evenly disperse the conductive carbon material and oxide solid electrolyte particles of various particle sizes in the second powder, coat them on the outer surface of the positive electrode active material particles and incorporate them into the fiberized binder together to obtain a third powder.
[0060] Specifically, in step 4, a supersonic airflow pulverizer is used to perform fiberization treatment on the second powder:
[0061] The second powder after pre-fiberization is added to the supersonic airflow pulverizer, and compressed air is generated through the nozzle to generate a supersonic airflow that is injected into the pulverizing chamber. The supersonic airflow velocity is greater than 300 m / s, so that the second powder is fluidized. The accelerated second powder converges at the intersection of the jet airflows of several nozzles, generating violent collisions, frictions and shearing, so that the secondary agglomerated particles of the conductive carbon material and the oxide solid electrolyte particles of various particle sizes are fully crushed and dispersed, and a uniformly dispersed conductive agent and solid electrolyte coating layer are formed on the surface of the active material particles, thereby forming a good conductive and ion-conducting network. At the same time, under the action of strong shear force, the uniformly dispersed binder is fully fiberized to obtain a fluffy binder structure, so that the well-dispersed active material coated with conductive carbon and solid electrolyte is incorporated into the fiber network to obtain the third powder.
[0062] Step 5: Perform multi-stage hot rolling processing on the third powder to obtain a first electrode membrane.
[0063] Specifically, step 5 is an electrode diaphragm manufacturing process, which is processed by a powder metering and conveying device and a multi-stage hot rolling equipment: the third powder is transmitted to the multi-stage hot rolling equipment through the powder metering and conveying device, and the working temperature of the heating roller is in the range of 150-250°C. During the multiple hot rolling processes, the fluffy third powder has binder fibers overlapping each other, extruding and moving to form a network structure, and the network structure wraps and bonds the other component particles together. After roller forming, hot pressing shaping, trimming and winding are performed to complete the entire hot pressing forming process, forming a first electrode diaphragm with uniform thickness, and the diaphragm is wound up for standby use.
[0064] The working temperature of the heating roller in step 5 is within the range of 150-250°C, which can ensure that the binder can be fully fiberized under the action of roller pressure and high temperature, so that the fibers overlap each other, build a continuous binder fiber network, and ensure the mechanical strength of the electrode membrane. This step can achieve precise control of the thickness of the electrode membrane by controlling the roller gap and pressure of the multi-stage roller.
[0065] Step 6: Repeat steps 1-5 to prepare a second electrode membrane.
[0066] It should be noted that step 6 adopts the same preparation process as the above steps 1-5. The difference between step 6 and step 1-5 is that the proportion of the conductive carbon material, oxide solid electrolyte particles of various particle sizes and binder added in step 6 to the mass of the electrode membrane is different from that in step 1-2.
[0067] Step 7: stack the carbon-coated aluminum foil current collector, the first electrode membrane, and the second electrode membrane in sequence, and perform hot roller pressing to obtain a high-load composite positive electrode sheet with a gradient distribution.
[0068] Specifically, the array-type through-hole carbon-coated aluminum foil current collector selected in step 7 is different from the general carbon-coated aluminum foil and aluminum foil current collector. The surface of the through-hole carbon-coated aluminum foil current collector of the present invention is processed by chemical or physical methods to form regularly arranged tiny through holes on the current collector to construct an array structure, which can increase the surface roughness of the current collector and effectively improve the adhesion between the electrode membrane and the current collector interface. This step realizes the control of the compaction of the composite positive electrode sheet by adjusting the roller gap width and the roller pressure.
[0069] On the basis of the above steps 1-7, the prepared high-load composite positive electrode sheet with gradient is assembled with a separator, a negative electrode sheet and an electrolyte to obtain a battery cell.
[0070] The present invention also describes a high-load composite positive electrode with a gradient, including an electrode membrane group and an array of through-hole carbon-coated aluminum foil current collectors near the inner layer of the electrode membrane group; the electrode membrane group includes a first electrode membrane arranged on the outer layer of the current collector and a second electrode membrane located on the inner layer. Figure 2 , Figure 2 This is a cross-sectional SEM image of a high-load composite positive electrode sheet with a gradient prepared by the above preparation method. It can be seen from the figure that the high-load composite positive electrode sheet is provided with a first electrode sheet, a second electrode sheet and an array-type through-hole carbon-coated aluminum foil current collector in sequence from bottom to top.
[0071] The thickness of the high-load composite positive electrode sheet with gradient is 30-500 μm.
[0072] The compaction density of the high-load composite positive electrode plate with gradient is related to the positive electrode material used. Taking NCM811 battery as an example, the preset range of the compaction density of the plate is 2.8-3.8 g / cm 3 .
[0073] It should be noted that, according to actual application requirements, the array-type through-hole carbon-coated aluminum foil current collector can be composited with the electrode membrane group on one side or on both sides.
[0074] The array-type through-hole carbon-coated aluminum foil current collector is composited with the electrode membrane group on one side, which can reduce the total weight of the positive electrode, has a low manufacturing cost, and has better flexibility, which makes it more suitable for applications that require a certain degree of bending or deformation. Application scenarios include: 1. Smartphones, laptops, and tablets, which usually require high energy density and lightweight design; 2. Flexible electronic products such as wearable devices and smart clothing, the single-sided composite structure allows greater design flexibility; 3. In power tools that require lightweight and high-rate charging and discharging, the electrode sheet with a single-sided composite structure has application potential.
[0075] The array-type through-hole carbon-coated aluminum foil current collector and the electrode membrane group are double-sidedly composited. Compared with the single-sided composite electrode membrane group, it can accommodate more active materials on the same current collector area, significantly improving the total capacity of the battery. The double-sided coating makes the electrochemical reaction of the electrode more balanced during the charge and discharge process, reduces polarization, and improves the overall performance of the battery; the force is more uniform during the cycle process, which can effectively reduce the deformation and peeling of the electrode material, thereby extending the service life of the battery; because the active material is distributed on both sides, the ion migration path is shortened, which can improve the rate performance of the battery. Application scenarios such as: 1. In electric vehicle batteries that require high energy density and high power output, the double-sided composite structure can meet its demanding performance requirements; 2. In energy storage systems that require large capacity and long life, such as grid peak regulation and home energy storage, the high capacity and stability of the double-sided composite electrode sheet are very critical; 3. In professional power tools that require high power density, batteries with double-sided composite structures can provide stronger output power and longer use time.
[0076] In general, single-sided composite array carbon-coated aluminum foil current collectors are more suitable for weight-sensitive consumer electronics and flexible electronic devices, with good flexibility and cost-effectiveness. Double-sided composite array carbon-coated aluminum foil current collectors are suitable for high-performance battery applications such as electric vehicles, energy storage systems, and high-power power tools, with higher energy density and better electrochemical performance. Depending on the actual application requirements, choosing a single-sided composite or double-sided composite carbon-coated aluminum foil current collector structure can effectively optimize battery performance and achieve the best battery design.
[0077] The high-load composite positive electrode plate with gradient of the present invention is applied to the fields of liquid lithium ion batteries and semi-solid batteries. For liquid lithium-ion batteries, a gradient-distributed dry-process high-load composite positive electrode sheet is used as the positive electrode material. Taking the single-sided composite array through-hole carbon-coated aluminum foil current collector of the positive electrode sheet as an example, the diaphragm is located on one side of the positive electrode sheet having the first electrode sheet, and the negative electrode sheet is arranged on the other side of the diaphragm; the liquid electrolyte is infiltrated in the diaphragm, and the first electrode sheet is the outer layer of the positive electrode sheet group, which is in direct contact with the electrolyte. This direct contact allows the lithium ions in the electrolyte to undergo an electrochemical reaction with the positive electrode material during the battery charging and discharging process. Since the first electrode sheet contains a higher proportion of oxide solid electrolyte particles than the second electrode sheet, it can stably conduct lithium ions and support electrode reactions, which helps to stabilize the interface between the electrolyte and the electrode material and reduce side reactions and interface impedance. The second electrode sheet located in the inner layer of the electrode membrane group contains a higher proportion of binder and conductive carbon material than the first electrode sheet, which enhances the electronic conductivity and supports the structure of the positive electrode material, so that the liquid lithium-ion battery has higher conductivity and stability. For semi-solid batteries, the difference from liquid lithium-ion batteries is that the electrolyte uses a mixture of solid electrolyte and a small amount of liquid or gel electrolyte, and the liquid electrolyte is converted into a gel state using an in-situ curing process. Its electrolyte content is different from that of liquid lithium-ion batteries. The electrolyte content of semi-solid batteries is usually between 5% and 10%.
[0078] Hereinafter, the embodiments of the present invention will be described in more detail by way of examples. However, the embodiments of the present invention are not limited only to these examples. Example 1
[0079] This embodiment provides a high-load composite positive electrode sheet with a gradient distribution and a preparation method thereof, and the method includes the following steps.
[0080] The raw materials for the first electrode plate were weighed, and four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), conductive carbon nanotubes (CNT), solid electrolyte (LATP), and binder polytetrafluoroethylene (PTFE), were weighed at a mass percentage of 91:2:5:2, wherein LATP was composed of nano-sized and micron-sized powders, and the powder ratio was 2:1. The raw materials for the second electrode plate were weighed, and four raw materials, namely, NCM811, CNT, LATP, and binder PTFE, were weighed at a mass percentage of 90:3:3:4, wherein LATP was composed of nano-sized and micron-sized powders, and the ratio of the two sizes of powders was 2:1.
[0081] First, add the three raw materials of NCM811, CNT and LATP into a powerful mixer, stir at a speed of 8000r / min for 60 min at room temperature, and mix the powders evenly to obtain the first powder. Pre-lower the temperature of the stirring tank to 5°C, add PTFE binder into the mixer, and stir at a lower speed of 500 r / min for 20 min to ensure that PTFE is evenly dispersed in the first powder to form the second powder. Take the second powder out of the stirring tank and place it in a high-temperature oven at 150°C for 4 h to pre-fiberize the binder and achieve the transformation of the crystal form, which is conducive to the subsequent full fiberization to obtain the third powder. Then add the third powder into the supersonic airflow pulverizer, and control the gas flow rate and pressure to ensure that the airflow speed exceeds 300 m / s, so as to achieve full dispersion of each component material and full fiberization of bonding, and obtain a fluffy powder. Finally, the fluffy powder is transferred to a multi-stage hot rolling device through a powder metering and conveying device. The rolling temperature is 200°C. After multiple hot rolling processes, the powder is rolled up to obtain a self-supporting first electrode sheet.
[0082] The related raw materials of the second electrode plate are mixed, sheared, rolled and processed according to the same steps as above to obtain the second electrode plate.
[0083] This embodiment provides a high-load composite positive electrode plate with a gradient distribution, including the above-mentioned first electrode plate, the second electrode plate and the array-type through-hole carbon-coated aluminum foil current collector, and the above-mentioned membrane and carbon-coated aluminum foil are hot-pressed and composited into one by hot rolling equipment. Example 2
[0084] This embodiment provides a high-load composite positive electrode sheet with a gradient distribution and a preparation method thereof, and the method includes the following steps.
[0085] The raw materials for the first electrode plate were weighed, and four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), conductive carbon nanotubes (CNT), solid electrolyte (LATP), and binder polytetrafluoroethylene (PTFE), were weighed at a mass percentage of 89:2:7:2, wherein LATP was composed of nano-sized and micron-sized powders, and the powder ratio was 2:1. The raw materials for the second electrode plate were weighed, and four raw materials, namely, NCM811, CNT, LATP, and binder PTFE, were weighed at a mass percentage of 89:3:3:5, wherein LATP was composed of nano-sized and micron-sized powders, and the ratio of the two sizes of powders was 2:1.
[0086] First, add the three raw materials of NCM811, CNT and LATP into a powerful mixer, stir at a speed of 10000r / min for 60 min at room temperature, and mix the powders evenly to obtain the first powder. Pre-lower the temperature of the stirring tank to 5°C, add PTFE binder into the mixer, and stir at a lower speed of 500 r / min for 20 min to ensure that PTFE is evenly dispersed in the first powder to form the second powder. Take the second powder out of the stirring tank and place it in a high-temperature oven at 150°C for 4 h to pre-fiberize the binder and achieve the transformation of the crystal form, which is conducive to the subsequent full fiberization to obtain the third powder. Then add the third powder to the supersonic airflow pulverizer, and control the gas flow rate and pressure to ensure that the airflow speed exceeds 300 m / s, so as to achieve full dispersion of each component material and full fiberization of bonding, and obtain a fluffy powder. Finally, the fluffy powder is transferred to a multi-stage hot rolling device through a powder metering and conveying device. The rolling temperature is 200°C. After multiple hot rolling processes, the powder is rolled up to obtain a self-supporting first electrode sheet.
[0087] The related raw materials of the second electrode plate are mixed, sheared and rolled according to the same steps as above to obtain the second electrode plate.
[0088] This embodiment provides a high-load composite positive electrode plate with a gradient distribution, including the above-mentioned first electrode plate, the second electrode plate and the array-type through-hole carbon-coated aluminum foil current collector, and the above-mentioned membrane and carbon-coated aluminum foil are hot-pressed and composited into one by hot rolling equipment.
[0089] Comparative Example 1:
[0090] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), carbon nanotubes, solid electrolyte (LATP) and binder polytetrafluoroethylene (PTFE), were weighed in a mass percentage of 93:2:3:2, wherein LATP was composed of nano-sized and micron-sized powders, and the powder ratio was 2:1. The above raw materials were added to a powerful mixer, stirred at a speed of 10,000 r / min for 60 min at room temperature, and the obtained powder was transferred to a multi-stage hot rolling device through a powder metering and conveying device, with a rolling temperature of 200°C. After multiple hot rolling, the self-supporting electrode membrane was obtained by winding.
[0091] This embodiment provides a positive electrode sheet, comprising the above-mentioned electrode membrane and a conventional carbon-coated aluminum foil, which is prepared by hot-pressing the above-mentioned positive electrode membrane onto the conventional carbon-coated aluminum foil using a hot rolling device.
[0092] Comparative Example 2:
[0093] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), conductive carbon nanotubes (CNT), solid electrolyte (LATP) and binder polytetrafluoroethylene (PTFE), were weighed in a mass percentage of 90:3:3:4, wherein LATP was composed of nano-sized and micron-sized powders with a powder ratio of 2:1.
[0094] First, add the three raw materials of NCM811, CNT and LATP into a powerful mixer, stir at a speed of 8000r / min for 60 minutes at room temperature, and obtain the first powder after the powder is evenly mixed. Pre-lower the temperature of the stirring tank to 5°C, add PTFE binder into the mixer, and stir at a lower speed of 500 r / min for 20 minutes to ensure that PTFE is evenly dispersed in the first powder to form the second powder. Take the second powder out of the stirring tank and place it in a high-temperature oven at 150°C for 4 hours to pre-fiberize the binder and achieve the transformation of the crystal form, which is conducive to the subsequent full fiberization to obtain the third powder.
[0095] Then, the third powder is added into the supersonic airflow pulverizer. By controlling the flow rate and pressure of compressed air, the airflow velocity is ensured to exceed 300 m / s, so as to achieve full dispersion and bonding of each component material and obtain fluffy powder.
[0096] Finally, the fluffy powder is transferred to a multi-stage hot rolling device through a powder metering and conveying device. The rolling temperature is 200°C. After multiple hot rolling processes, the powder is rolled up to obtain a self-supporting electrode membrane.
[0097] This embodiment provides a positive electrode sheet, including the above-mentioned electrode membrane and conventional carbon-coated aluminum foil, which is prepared by hot-pressing the above-mentioned positive electrode membrane onto the conventional carbon-coated aluminum foil through a hot rolling device. This electrode with a gradient structure design optimizes the ion transmission and electron transmission paths of the electrode through different levels of material composition, significantly improving the overall performance of the battery.
[0098] Comparative Example 3:
[0099] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), carbon nanotubes (CNT), solid electrolyte (LATP) and binder polytetrafluoroethylene (PTFE), were weighed in a mass percentage of 93:2:3:2, wherein LATP was a micron-sized powder. First, the three raw materials, NCM811, CNT and LATP, were added to a powerful mixer and stirred at a speed of 8000 r / min for 60 min at room temperature to obtain the first powder after the powders were evenly mixed.
[0100] The temperature of the stirring tank is lowered to 5°C in advance, and PTFE binder is added to the mixer. Stir at a low speed of 500 r / min for 20 min to ensure that PTFE is evenly dispersed in the first powder to form the second powder. The second powder is taken out of the stirring tank and placed in a high-temperature oven at 150°C for 4 h to pre-fiberize the binder and achieve the transformation of the crystal form, which is conducive to the subsequent full fiberization to obtain the third powder. The third powder is then added to the supersonic airflow pulverizer. By controlling the compressed air flow rate and pressure, the air flow rate is ensured to exceed 300 m / s to achieve full dispersion of each component material and full fiberization of bonding to obtain a fluffy powder. Finally, the fluffy powder is transferred to the multi-stage hot roller pressing equipment through the powder metering and conveying device. The roller pressing temperature is 200°C. After multiple hot roller pressings, the self-supporting electrode membrane is obtained by winding.
[0101] This embodiment provides a positive electrode sheet, comprising the above-mentioned electrode membrane and a conventional carbon-coated aluminum foil, which is prepared by hot-pressing the above-mentioned positive electrode membrane onto the conventional carbon-coated aluminum foil using a hot rolling device.
[0102] Comparative Example 4:
[0103] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), conductive carbon SP, solid electrolyte (LATP) and binder polytetrafluoroethylene (PTFE), were weighed in a mass percentage of 93:2:3:2, wherein LATP was composed of nano-sized and micron-sized powders with a powder ratio of 2:1.
[0104] First, add the three raw materials NCM811, SP and LATP into a powerful mixer, stir at a speed of 8000 r / min for 60 min at room temperature, and mix the powders to obtain the first powder. Pre-lower the temperature of the stirring tank to 5°C, add PTFE binder into the mixer, and stir at a lower speed of 500 r / min for 20 min to ensure that PTFE is evenly dispersed in the first powder to form the second powder. Take the second powder out of the stirring tank and place it in a high-temperature oven at 150°C for 4 h to pre-fiberize the binder and achieve the transformation of the crystal form, which is conducive to the subsequent full fiberization to obtain the third powder. Then add the third powder to the supersonic airflow pulverizer, and control the compressed air flow rate and pressure to ensure that the airflow speed exceeds 300 m / s to achieve full dispersion of each component material and full fiberization of bonding, and obtain a fluffy powder. Finally, the fluffy powder is transferred to a multi-stage hot rolling device through a powder metering and conveying device. The rolling temperature is 200°C. After multiple hot rolling processes, the powder is rolled up to obtain a self-supporting electrode membrane.
[0105] This embodiment provides a positive electrode sheet, comprising the above-mentioned electrode membrane and a conventional carbon-coated aluminum foil, which is prepared by hot-pressing the above-mentioned positive electrode membrane onto the conventional carbon-coated aluminum foil using a hot rolling device.
[0106] Comparative Example 5:
[0107] Four raw materials, namely, lithium nickel cobalt manganese oxide (NCM811), carbon nanotubes, solid electrolyte (LATP) and binder polytetrafluoroethylene (PTFE), were weighed in a mass percentage of 93:2:3:2, wherein LATP was composed of nano-sized and micron-sized powders with a powder ratio of 2:1. First, the above raw materials were added to a powerful mixer and stirred at a speed of 8000 r / min for 60 min at room temperature. The obtained powder was added to a supersonic airflow mill, and the airflow velocity was controlled to exceed 300 m / s by controlling the compressed air flow rate and pressure to obtain a fluffy powder. Finally, the fluffy powder was transferred to a multi-stage hot rolling device through a powder metering and conveying device, and the rolling temperature was 200°C. After multiple hot rolling, the self-supporting electrode membrane was obtained by winding.
[0108] This embodiment provides a positive electrode sheet, comprising the above-mentioned electrode membrane and a conventional carbon-coated aluminum foil, which is prepared by hot-pressing the above-mentioned positive electrode membrane onto the conventional carbon-coated aluminum foil using a hot rolling device.
[0109] Performance Testing:
[0110] The battery electrodes prepared in Examples 1-2 and Comparative Examples 1-5 were tested using the same testing equipment and testing standards to conduct electrode resistance testing, peel strength testing, and electrochemical performance testing. The specific testing methods are as follows:
[0111] Electrode piece resistance test: It is carried out in a electrode piece resistance meter. At room temperature of 25°C and air humidity of -40°C dew point, the prepared battery electrode is placed on the resistance meter table to make its surface flat. The pressure gauge is adjusted to fix the test sample to ensure good contact between the probe and the sample to obtain the resistance value of the electrode.
[0112] Peel strength test: It is carried out in a peel force tester. At room temperature of 25°C and air humidity of -40°C dew point in the room, one side of the prepared battery electrode collector is adhered to the working panel with a test double-sided tape, and the active material surface and the peel force tester are connected with a test tape. The peeling speed is 60 mm / min, the peeling angle is 180°, and the peeling force is tested and recorded.
[0113] Electrochemical performance test: Assemble the dry composite positive electrode sheet, metal lithium negative electrode, separator and electrolyte into a button battery, charge at a rate of 0.1 C and discharge at a rate of 0.1 C at 25°C to evaluate the capacity of the dry composite positive electrode sheet. Charge at a rate of 0.2 C and discharge at a rate of 0.5 C at 25°C, cycle each embodiment and comparative example 300 times, record the battery capacity before and after the cycle, and calculate the capacity retention rate. At 25°C, charge and discharge the button battery at different rates, record the discharge capacity and specific capacity at each rate, and calculate the capacity retention rate at each rate.
[0114] Refer to the instruction manual Figure 3-6 , Figure 3 The graph of the relationship between the battery capacity and the number of cycles of Example 1 is shown in FIG. Figure 3 As can be seen, the battery's surface capacity is 8.5 mAh / cm 2 The battery can be charged and discharged well in a cycle, and the capacity retention rate is about 98% after 40 cycles, indicating that the battery still has good cycle performance under extremely high load.
[0115] Figure 4 The voltage-specific capacity curves of Example 1 and Comparative Example 1 are shown in FIG. Figure 4 It can be seen that: within the same voltage range, the discharge specific capacity of Example 1 reaches about 208 mAh / g, and the discharge specific capacity of Comparative Example 1 is about 192 mAh / g, which shows that Example 1 has a higher discharge capacity under the same charge and discharge conditions, indicating that the construction of the gradient distribution high-load composite positive electrode sheet can give full play to the electrochemical properties of the active material.
[0116] Performance comparison: Energy density: Example 1 has a higher specific capacity within the same voltage range, so its energy density is significantly better than that of Comparative Example 1. The improvement in energy density means that Example 1 can store more energy in a battery of the same volume or weight. Practical application: These advantages of Example 1 make it more suitable for application scenarios that require high energy density and high efficiency, such as electric vehicles and portable electronic devices.
[0117] Figure 5 (a) shows the performance comparison between Example 1 and Comparative Example 1 at different cycle times. Figure 5 a is the change of capacity with the number of cycles; Figure 5 In (a), the capacity of Example 1 remains relatively stable during the entire cycle process. Although it decreases, the overall decrease is small; the capacity of Comparative Example 1 decreases significantly with the increase in the number of cycles, showing poor cycle stability; the 80% SOC line shows that at about 200 cycles, the capacity of Comparative Example 1 has dropped to 80%, while the capacity of Example 1 still remains at a high level. Figure 5 (b) shows the change of capacity retention rate with the number of cycles; Figure 5 The capacity retention rate of Example 1 in (b) decreases slowly during the entire cycle, showing better cycle stability; Figure 5 The capacity retention rate of Comparative Example 1 in (b) decreases faster, indicating that its performance degradation is more serious after multiple cycles. Example 1 is significantly better than Comparative Example 1 in terms of cycle stability and life, showing better battery performance and durability. Figure 5 (a) and (b) together demonstrate this advantage, making Example 1 more suitable for application scenarios requiring long life and high stability.
[0118] Figure 6 The discharge specific capacity (mAh / g) of Example 1 and Comparative Example 1 at different discharge rates (C rates) is compared. The discharge specific capacity of Example 1 at each discharge rate is higher than that of Comparative Example 1, especially at high rate discharge (such as 1C and 2C), the advantage of Example 1 is more obvious. Example 1 has a stronger capacity retention ability under high rate discharge conditions, which shows that its electrode material can function more effectively at high rates. The capacity of Comparative Example 1 decreases faster at high rate discharge, showing poor high rate discharge performance. Therefore, Example 1 has higher application value and competitiveness in practical applications, especially in situations where high rate discharge is required, such as power tools and electric vehicles.
[0119] The examples 1-2 and comparative examples 1-5 were tested according to the above test method to obtain the data in Table 1:
[0120] Table 1
[0121] Group Electrode sheet resistance (Ω·cm) Peel strength (N / m) 0.1C discharge specific capacity (mAh / g) 1C discharge specific capacity (mAh / g) Capacity retention rate after 200 cycles % Example 1 16.8 43.4 208.9 179.3 90.1 Example 2 17.3 45.7 205.1 176.7 91.4 Comparative Example 1 44.6 9.7 191.2 145.9 81.5 Comparative Example 2 21.3 23.8 198.7 165.9 87.5 Comparative Example 3 24.5 21.3 193.3 154.8 85.9 Comparative Example 4 303.1 18.9 181.6 72.6 15.3 Comparative Example 5 34.7 16.7 195.4 160.2 83.2
[0122] From Table 1 we can see that:
[0123] Pole sheet resistance: The pole sheet resistance of Example 1 and Example 2 is 16.8 cm and 17.3 cm, which is significantly lower than the resistance values of all comparative examples, especially the resistance values of comparative examples 4 and 5 are as high as 303.1 cm and 34.7 This indicates that the electrodes of Example 1 and Example 2 have better conductivity and are conducive to the rapid conduction of electrons.
[0124] Peel strength: The peel strengths of Example 1 and Example 2 are 43.4 N / m and 45.7 N / m, respectively, which are much higher than the peel strengths of all comparative examples, especially the peel strength of Comparative Example 1 is only 9.7 N / m. This shows that the electrode membranes of Example 1 and Example 2 have stronger adhesion to the current collector and are less likely to fall off.
[0125] 0.1C discharge specific capacity: The 0.1C discharge specific capacity of Example 1 and Example 2 is 208.9 mAh / g and 205.1 mAh / g, respectively, which is higher than the discharge specific capacity of all comparative examples. This means that under low rate discharge conditions, the batteries of Example 1 and Example 2 have higher energy density.
[0126] 1C discharge specific capacity: The 1C discharge specific capacity of Example 1 and Example 2 is 179.3 mAh / g and 176.7 mAh / g, respectively, which is significantly higher than the discharge specific capacity of Comparative Examples 1 to 5. This shows that under high rate discharge conditions, the batteries of Example 1 and Example 2 can still maintain a relatively high capacity and have superior performance.
[0127] Capacity retention rate after 200 cycles: The capacity retention rates of Example 1 and Example 2 are 90.1% and 91.4%, respectively, which are significantly higher than all comparative examples. In particular, the capacity retention rate of Comparative Example 4 is only 15.3%. This shows that the batteries of Example 1 and Example 2 have better stability and durability after long-term cycling.
[0128] In summary, Examples 1-2 show superior performance in terms of resistance, peel strength, discharge specific capacity and cycle life, and are significantly better than Comparative Examples 1-5.
[0129] The preparation method of the present invention adopts step-by-step mixing, pre-fiberization and strong shear mixing technology to achieve uniform mixing of active materials, conductive carbon materials, oxide solid electrolyte particles and binder components, and achieve sufficient and uniform fiberization of the binder, thereby improving the strength of the electrode film and being able to accurately control the electrode thickness and uniformity. The oxide solid electrolyte particles are mixed with different particle sizes to construct an efficient and continuous ion and electron transmission network inside the thick electrode sheet, thereby reducing the polarization of the electrode sheet, improving the battery rate charge and discharge performance and the gram capacity of the active material, and constructing a multi-gradient electrode by preparing different electrode layers to improve the adhesion between the electrode and the current collector. An array-type through-hole carbon-coated aluminum foil is used to replace the conventional aluminum foil current collector, thereby improving the adhesion between the electrode membrane and the current collector, reducing the interface resistance, reducing the internal resistance of the battery, and at the same time reducing the weight of the current collector, thereby improving the battery energy density.
[0130] The above is only an embodiment of the present invention, and the common sense such as the known specific structure and characteristics in the scheme is not described in detail here. For those skilled in the art, it is obvious that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic characteristics of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the present invention is defined by the attached claims rather than the above description, so it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Any figure mark in the claims should not be regarded as limiting the claims involved.
Claims
1. A method for preparing a dry high-load composite positive electrode sheet with a gradient distribution, characterized in that: The preparation method comprises the following steps: Step 1: premixing the conductive carbon material, oxide solid electrolyte particles of various particle sizes, and the positive electrode active material in a certain proportion, and dispersing them at a stirring speed of 5000-10000 r / min to obtain a first powder; Step 2: adding a certain amount of binder to the first powder, dispersing the mixture under the conditions of a stirring speed of 200-800 r / min and a stirring temperature of 0-10° C. to obtain a second powder; Step 3: heat-treating the second powder at a temperature of 90-200° C. to obtain a pre-fiberized second powder; Step 4: using a supersonic airflow with a speed greater than 300 m / s to treat the second powder after heat preservation, fiberizing the binder material, and uniformly dispersing and coating the conductive carbon material and multi-size oxide solid electrolyte particles on the surface of the positive electrode active material particles to form a third powder coated with a fiberized binder; Step 5: performing a multi-stage hot roller pressing process on the third powder to obtain a first electrode membrane; Step 6: Repeat the method of steps 1-5, gradually adjust the ratio of different components in the first electrode membrane, and prepare a second electrode membrane; Step 7: stacking the carbon-coated aluminum foil current collector, the first electrode membrane, and the second electrode membrane in sequence, and performing hot roller pressing treatment to obtain a high-load composite positive electrode sheet with a gradient distribution; In step 1, the particle sizes of the plurality of oxide solid electrolytes include at least two types: micron particles and nanoparticles; In step 6, the mass proportion of the binder and the conductive carbon material of the second electrode membrane is greater than the mass proportion of the binder and the conductive agent of the first electrode membrane, and the mass proportion of the oxide solid electrolyte particles of the second electrode membrane is less than the mass proportion of the oxide solid electrolyte particles of the first electrode membrane; In step 7, an array-type through-hole structure is provided on the carbon-coated aluminum foil current collector.
2. The method for preparing a dry high-load composite positive electrode sheet with a gradient distribution according to claim 1, characterized in that: The amount of conductive carbon material added is 1-6wt% of the mass of the high-loaded composite positive electrode sheet, the amount of the mixture of oxide solid electrolyte particles of various particle sizes added is 1-10wt% of the mass of the high-loaded composite positive electrode sheet, the amount of positive electrode active material added is 77-96wt% of the mass of the high-loaded composite positive electrode sheet, and the amount of binder added is 2-7wt% of the mass of the high-loaded composite positive electrode sheet.
3. The method for preparing a dry high-load composite positive electrode sheet with gradient distribution according to claim 1, characterized in that: The particle size range of micron particles is 1-5 μm, the particle size range of nanoparticles is 100-600 nm, and the mixing ratio of nanoparticles to microparticles is in the range of 5:1-1:
1.
4. The method for preparing a dry high-load composite positive electrode sheet with gradient distribution according to claim 1, characterized in that: In step 1, the conductive carbon material is a carbon material with a high aspect ratio and high conductivity.
5. The method for preparing a dry high-load composite positive electrode sheet with gradient distribution according to claim 1, characterized in that: The stirring time in step 1 is 30-300 min, and the stirring temperature is room temperature; the stirring time in step 2 is 10-60 min.
6. The method for preparing a dry high-load composite positive electrode sheet with gradient distribution according to claim 1, characterized in that: The holding time in step 3 is 2-10 h; the working temperature of the heating roller in step 5 is 150-250°C.
7. A dry high-load composite positive electrode sheet with gradient distribution, characterized in that: The dry high-load composite positive electrode sheet is prepared by the preparation method described in any one of claims 1-6; it includes an electrode membrane group and an array-type through-hole carbon-coated aluminum foil current collector close to the inner layer of the electrode membrane group; the electrode membrane group includes a first electrode membrane arranged on the outer layer of the current collector and a second electrode membrane located on the inner layer.
8. The dry-process high-load composite positive electrode sheet with gradient distribution according to claim 7, characterized in that: The gradient distribution of the dry-process high-load composite positive electrode sheet is that the mass proportion of the oxide solid electrolyte particles gradually decreases from the first electrode membrane to the second electrode membrane, and the mass proportion of the conductive carbon material and the binder gradually increases from the first electrode membrane to the second electrode membrane; the thickness of the dry-process high-load composite positive electrode sheet is 30-500μm.
Citation Information
Patent Citations
Method for preparing electrode membrane of lithium ion battery by dry method
CN115579458A
Thick electrode and preparation method and application thereof
CN115939300A
Pole piece, preparation method of pole piece, battery, battery module, battery pack and device
CN117352651A
Lithium ion battery positive electrode slurry and preparation method thereof
CN118431405A
Collector material, and method of manufacturing the same
JP2008283152A